In Vitro Antioxidant, Anti-Inflammatory, Anthelmintic, Anti-Microbial, FTIR and TLC Analysis of the Leaves of Memecylon amoenum - Buah, Patrick; Acheampong, Akwasi; Amengor, Cedric Dzidzor; Oti-Boakye, Adolf; Baah, Kennedy Ameyaw; Odei, Judith; Acheampong, Lydia Opoku; Sarfo-Mainoo, Lydia Tima (Sciences of Phytochemistry, 2026)
Memecylon amoenum is traditionally employed across West Africa for treating waist pains, diarrhoea, wounds, toothache and various skin ailments. The study aimed to identify major phytoconstituents using standard phytochemical screening, chromatographic separation, and FTIR analysis and to evaluate the biological activities of the methanol and petroleum ether leaves extracts. Phytochemical investigations revealed twelve constituents in the pulverized plant material and eleven in the methanolic extract, while the petroleum ether extract contained six. In the DPPH assay, the methanol and petroleum ether extracts of M. amoenum demonstrated IC₅₀ values of 11.42 ± 0.05 and 43.42 ± 0.62 µg/mL, respectively, outperforming ascorbic acid (58.46 ± 0.8 µg/mL). Total antioxidant capacity values (gAAE/100 g) were 36.04 ± 1.43 for the hetmethanol extract and 31.35 ± 3.98 for the petroleum extract. The extracts also exhibited potent anthelmintic activity, surpassing mebendazole at all tested concentrations for example the death time at 6mg/mL are 2min 05s, 4min 16s and 8min 33s respectively for the methanol extract, pet-ether extract and mebendazole. Both extracts showed broad antimicrobial effects, with minimum inhibition concentrations, 0.0122 to 25 mg/mL, and demonstrated notable anti-inflammatory properties. Thin-layer chromatographic profiling revealed four spots in the methanolic extract and seven in the petroleum ether extract, suggesting chemical diversity between the solvent fractions. FTIR spectra confirmed the presence of functional groups consistent with the compounds detected through phytochemical screening. The results indicate that the methanol and petroleum ether extracts of M. amoenum possess significant antioxidant, anti-inflammatory, antimicrobial and anthelmintic activities, supporting their potential as therapeutic effect.